Diagnosing lung involvement in inflammatory rheumatic diseases—Where do we currently stand? - Hoffmann, Tobias; Oelzner, Peter; Teichgräber, Ulf; Franz, Marcus; Gaßler, Nikolaus; Kroegel, Claus; Wolf, Gunter; Pfeil, Alexander (Frontiers in Medicine, 2023)
Lung involvement is the most common and serious organ manifestation in patients with inflammatory rheumatic disease (IRD). The type of pulmonary involvement can differ, but the most frequent is interstitial lung disease (ILD). The clinical manifestations of IRD-ILD and severity can vary from subclinical abnormality to dyspnea, respiratory failure, and death. Consequently, early detection is of significant importance. Pulmonary function test (PFT) including diffusing capacity of carbon monoxide (DLCO) and forced vital capacity (FVC) as well as high-resolution computed tomography (HRCT) are the standard tools for screening and monitoring of ILD in IRD-patients. Especially, the diagnostic accuracy of HRCT is considered to be high. Magnetic resonance imaging (MRI) and positron emission tomography/computed tomography (PET/CT) allow both morphological and functional assessment of the lungs. In addition, biomarkers (e.g. KL-6, CCL2 or MUC5B) are being currently evaluated for the detection and prognostic assessment of ILD. Despite the accuracy of HRCT, invasive diagnostic methods such as bronchoalveolar lavage (BAL) and lung biopsy are still important in clinical practice. However, their therapeutic and prognostic relevance remains unclear. The aim of this review is to give an overview of the individual methods and to present their respective advantages and disadvantages in detecting and monitoring ILD in IRD-patients in the clinical routine.